Koeleria moldavica (Poaceae): geographical distribution, ecological habitat conditions and coenotical peculiarities (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Based on the results of own floristic studies, elaboration of herbarium collections from herbarium KW, KRW, CWU, YALT and according to the literary data, the chorology of a rare endemic species Koeleria moldavica in Ukraine and the Republic of Moldova is presented. The species is more widespread than previously thought. In general, K. moldavica habitat covers the steppe regions of the Black Sea Lowland and forest-steppe regions of the southern part of Podilia upland. The ecological characteristic of the habitat of the species is given. Koeleria moldavicа is exclusively limited to limestone outcrops of mainly the middle reaches of the Dniester, Ingul, Ingulets and lower Dnieper regions, where it grows on primitive and poor sod-steppe soils. There are five locations of the species in the lower part of the Dnieper valley, six localities in the Ingulets valley and Vysun river, five localities in the Ingul valley and four in Odessa region. In Republic of Moldova, twelve localities were known mostly in the middle part of the Dniester as vicinity of Rybnitsa and the Yagorlyk River basin. Koeleria moldavica does not form its own formation, rarely it is a subdominant, and often as an assectator. The species is also an important component of many associations of rare formations as Jurineeta brachycephalae, Stipeta capillatae, S. lessingianae, S. asperellae, S. ucrainicae, Botriochloeta ischaemi, Chamaecytiseta granitici, Elytrigieta stipifoliae or Galatelleta villosae. The main anthropogenic and natural factors that lead to the reduction of Koeleria moldavica populations of the species are indicated. To preserve K. moldavicа populations, it is proposed to create new nature conservation reserves in the Odesa, Mykolaiv and Kherson regions and to include the species in the Red Data Book of Ukraine.
Keywords: endemic species, chorology, Northern Black Sea Region, limestone outcrops, rare communities, conservation.